Teoría del Género Literario Narrativo para la creación de un cuento - Araujo Luján, Michelle Alessia (2022)
This research of professional proficiency is based on the teaching-learning process in the area of Communication, with the intention of developing the competence: write different types of texts in their mother language. Of course, the student will have to reach certain standards to demonstrate that he/she has learned according to the pedagogical intentions of the teacher. For this, the main support will be the theory of Literary Genres, understood as an element that allows differentiating and recognizing the different types of literary texts, since the author knows beforehand what form, elements and characteristics should present what he/she is going to produce. In this sense, inculcating this practice in young students has vital importance to perpetuate the literary dynamics. For this purpose, a specific form will be used, belonging to the Narrative Literary Genre, which is the short story. These texts are among the best known and transmit a great deal of familiarity. Approaching them at a theoretical level and managing to produce them, writing them, will facilitate a sort of initiation into the artistic world, and consequently, the literary one.